An interesting denaro tornese of the Barons Revolt of 1459-1464 and some considerations regarding Nicola II di Monforte - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2018)
In the summer of 2016 it came to my attention that a German dealer had put up for auction a denaro tornese minted under the authority of Nicola II di Monforte, one of the leaders of the Barons Revolt (La Congiura dei Baroni) between 1459 and 1464 against Ferdinand I of Naples.